Modifikasi Model Edukasi Meja Putar Sebagai Upaya Meningkatkan Tindakan Dalam Memelihara Kesehatan Gigi Pada Siswa - Yulyana Sendia Martina; Dwi Septiarini; Rohisotul Laily; Hayatunnufus (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2025)
Dental caries is a multifactorial disease that causes demineralization of the tough tissues of the teeth. One of the factors that contribute to tooth decay is poor behavior. 80% of the students in SD Yapita Surabaya School suffer from dental caries, with an average caries index reaching the "poor" level of 2.2. This problem can be addressed by modifying the turntable teaching model, which can achieve fun and educational learning, thus making the learning process interesting. The aim of this research is to develop a practical and effective modified version of the Turntable teaching model to improve the dental health of students in SD Yapita Surabaya. The research method used is Research and Development with a true experiment research design (pretest-posttest). The sample consisted of 60 respondents including before treatment group and the after treatment group. The data from the model test results used paired t-test. Results: The modified Turntable teaching model was tested by experts for validation, and the inter-class correlation coefficient P value was 0.001. Modification of the Turntable Education Model is feasible and its implementation is effective as an effort to improve actions in maintaining dental health in students at SD Yapita Surabaya in the group after treatment compared to the group before treatment. Keywords: Actions; dental health; primary school students; turntable